Sekar Ayu Boga's Business Strategy To Increasing Competitive Advantage In Covid-19 Pandemic - Rina Rachmawati; Fedy Setyo Pribad; Siti Fathonah (Jurnal Pendidikan Tata Boga dan Teknologi, 2020)
Sekar Ayu Boga is a business owned by the Study Program of Culinary Education at the Department of home economics which was founded in 2003. This business, starting in 2018, received grants from the Campus Intellectual Product Business Development Program (PPUPIK). Sekar Ayu Boga is currently experiencing business difficulties due to the COVID 19 pandemic. This article aims to identify Sekar Ayu Boga's efforts and discuss the solutions in dealing with the Covid 19 Pandemic. The results of the situation analysis are used to determine alternative strategies to maintain business, including increasing product quality without preservatives to increase consumer loyalty, create new products that are more relevant to the conditions of the Covid 19 pandemic era and carry out online promotions by making the  sekaraayuboga.com website that hopefully as a medium to expand consumer reach. These three strategies are a combination chosen to strengthen business strategies so as to increase the competitive advantage of Sekar Ayu Boga Unnes.